Strategi Keluarga dalam Menyiapkan Suksesi: Analisis Terhadap Proses Perencanaan dan Pelaksanaan - Moch. Wahyu Widodo; Sudarmiatin Sudarmiatin; Ludi Wishnu Wardana (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the planning and succession process in the Medali Mas ikat weaving family business. The research approach used is qualitative descriptive. The types of data used are primary and secondary data. Data collection techniques are carried out by observation, interviews, documentation. The research results show that the succession process was carried out with careful planning. Children as potential replacements are guided by their parents from childhood to be ready to continue the family business. Apart from that, children are required to go to college to increase their knowledge for managing the family business.